Empowerment in Cancer Care- Adaptation of the Patient Empowerment Scale and Its Associations with Mental Health, Quality of Life, and Coping Strategies - Paleczna, Monika; Gruszka, Jan; Bulsara, Caroline (Polish Psychological Bulletin, 2026)
Patient empowerment has been linked to physical health outcomes and recovery; however, its relationship with mental health remains insufficiently explored, particularly in oncology populations, as most prior research has focused on non-oncology patients. Given the growing number of individuals diagnosed with cancer, this gap warrants investigation. This study examined the associations between overall patient empowerment and key indicators of mental functioning in oncology patients undergoing treatment, and aimed to develop a Polish adaptation of the Patient Empowerment Scale (PES). The analyzed indicators- coping strategies, health locus of control, quality of life, anxiety, depression, and post-traumatic growth- correspond to the intrapersonal, interactional, and behavioral components of psychological empowerment as conceptualized by Zimmerman. The sample comprised 120 patients (65 women, 55 men; aged 30-83). Measures included the PES, MINI-MAC, MHLC, EORTC QLQ-C30, HADS-M, and PTGI. Empowerment was significantly associated with all examined psychological indicators. The findings enhance understanding of psychosocial functioning in cancer patients and support the development of empowerment-based psychological interventions. The study also resulted in the development of PES-PL, a Polish adaptation of the Patient Empowerment Scale.